Determination of stress and displacement on human composite pelvis under static and dynamic loading - Beneš, Jan; Kunz, Ludvík; Liška, Jiří; Šrám, Jaroslav; Krbec, Martin; Džupa, Valér; Křivohlávek, Martin; Návrat, Tomáš (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2022)
This case study describes the experimental determination of displacements and stresses on a composite model of a pelvis that was modified to represent a healthy intact pelvic ring. The modified model was stressed statically up to 1750 N to simulate standing on one leg and also cyclically to model walking. For two different model settings in the loading machine the values of displacements and stresses at the pelvic ring were determined. The two different settings correspond to two different loading vectors applied on the pelvic ring, boundary conditions and degrees of freedom. The experimentally determined values of displacements in both settings are very similar and in accordance with the knowledge on the behaviour of a real human pelvis. The modified model is thus suitable for testing of newly developed implants for pelvis treatment and experimental determination of displacements and stresses in pelvic ring which are caused by application of implants.
Keywords: biomechanika; Biomechanical Phenomena; acetabulum; Pelvic Bones; Pelvis; Pelvic trauma; composite pelvic model; Humans; stress and displacement in pelvis; pánevní kosti; pubic symphysis; pánev; lidé; sacroiliac joint